CD8(+) T-cell responses to Theileria parva are preferentially directed to a single dominant antigen: Implications for parasite strain-specific immunity - MacHugh, Niall D (WILEY-VCH Verlag, 2009)
Although immunodominance of CD8(+) T-cell responses is a well-recognised feature of viral infections, its role in responses to more antigenically complex pathogens is less clear. In previous studies we have observed that CD8(+) T-cell responses to Theileria parva exhibit different patterns of parasite strain specificity in cattle of different MHC genotypes. In the current study, we demonstrated that animals homozygous for the A10 and A18 MHC haplotypes have detectable responses to only one of 5 T. parva antigens. Over 60% of the responding T cells from the A18(+) and A10(+) animals recognised defined epitopes in the Tp1 and Tp2 antigens, respectively. Comparison of T-cell receptor β chain expression profiles of CD8(+) T-cell lines and CD8(+) T cells harvested ex vivo confirmed that the composition of the T-cell lines was representative of the in vivo memory CD8(+) T-cell populations. Analysis of the Tp1 and Tp2 antigens revealed sequence polymorphism, which was reflected by differential recognition by T-cell lines. In conclusion, we have demonstrated a profound immunodominance in the CD8(+) T-cell response to T. parva, which we propose is a major determinant of the parasite strain specificity of the response and hence immune protection.